Kontribusi Pemikiran John Wesley Mengenai Penerapan Disiplin Rohani Melalui Pendidikan Agama Kristen di Sekolah Dasar - Jimson Sitorus; Anen Mangapul Situmorang; Debora Inda Violita Praing (Jurnal Shanan, 2022)
Fulfillment of physical needs must take place in balance with spiritual needs. However, these spiritual needs are sometimes neglected. The reason, that certain followers of Christ are too preoccupied with fulfilling biological needs. Spiritual aspects such as not a need. According to this problem, the purpose of this paper is to analyze the contribution of John Wesley's thoughts on the application of spiritual discipline through Christian Religious Education in elementary schools. It is necessary to apply spiritual discipline since childhood in order to maintain a balance between the human spiritual needs and the fulfillment of physical needs. The method used, qualitative through a literature study. This research describes the application of spiritual discipline as a contribution of John Wesley's thoughts and CRE in elementary schools. The results show, on the application of spiritual disciplines such as prayer, digging into the Bible, sacraments and social life are emphasized in CRE in elementary schools. This can be seen through several sources such as the curriculum and textbooks used. Concretely, the application of spiritual discipline in elementary schools, among others; the habit of praying, singing spiritual songs, reading the Bible, including extracurricular activities for fostering Christian faith in addition to class activities.